Principales enfermedades en el cultivo de la gulupa y su manejo :(Passiflora edulis f. edulis sims) - Villegas Estrada, Bernardo; Ocampo Pérez, John; Castillo Londoño, Carlos Fernando; Wyckhuys, Kris; Villegas Estrada, Bernardo (Universidad Jorge Tadeo Lozano, 2018)
Gulupa-Passiflora ligularis